2012
DOI: 10.17221/6363-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary organic acid blend supplementation and interaction with delayed feed access after hatch on broiler growth performance and intestinal health

Abstract: ABSTRACT:A trial was conducted to investigate the effects of a dietary organic acid blend for a period of 35 days on the growth performance, intestinal histomorphology and microflora of male broiler chicks with delayed access to feed. One hundred and ninety two one day old broiler chicks (ROSS 308) were randomly distributed into 4 groups housed in four replicate pens with 12 birds in each. A 2 × 2 factorial design was implemented. Four experimental groups were formed by two levels of dietary organic acid blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Higher gain was associated with higher feed intake. Cengiz et al (2012) reported that supplementation of organic acids to poultry diets was shown to increases beneficial microbial activity in the small intestine. It also suppresses the growth of certain species of bacteria such as Salmonella, E. coli, Clostridium perfringes, Listeria monocytogenes and Campylobacter (Van Immerseel et al, 2002;Hassan et al, 2010;Mohamed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Higher gain was associated with higher feed intake. Cengiz et al (2012) reported that supplementation of organic acids to poultry diets was shown to increases beneficial microbial activity in the small intestine. It also suppresses the growth of certain species of bacteria such as Salmonella, E. coli, Clostridium perfringes, Listeria monocytogenes and Campylobacter (Van Immerseel et al, 2002;Hassan et al, 2010;Mohamed et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the caeca were ligated and carefully hand-stripped into sterile plastic bags. In the present study, total aerobic bacteria, Escherichia coli, coliforms, and lactobacilli were enumerated in the caecal digesta samples according to the procedures previously described by Cengiz et al (2012). The caecal digesta samples were appropriately stored at -80 ºC.…”
Section: Caecal Microbe Countmentioning
confidence: 99%
“…Several studies have suggested that organic acid supplementation to poultry diets acts as a bactericidal for Salmonella in the crop (Thompson & Hinton 1997), ceca and small intestine (Vogt et al, 1982) and ileum (Cengiz et al, 2012), thus providing better intestinal health for the bird to obtain maximum nutrient absorption. Organic acid supplementation to poultry diets has been shown to suppress the growth of certain species of bacteria, mainly acid-intolerant species such as Salmonella, E. coli, Clostridium perfringes, Listeria monocytogenes and Campylobacter (Van Immerseel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%